2018
DOI: 10.1007/978-1-4939-8976-8_30
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Method for the Study of Antibody Neutralization of HCV Pseudoparticles (HCVpp)

Abstract: Hepatitis C virus (HCV) pseudoparticles (HCVpp) are generated by cotransfection of HCV envelope (E1 and E2) genes along with a retroviral packaging/reporter construct into HEK293T cells. Enveloped particles bearing HCV E1E2 proteins on their surface are released through a retroviral budding process into the supernatant. Viral E1E2 glycoproteins facilitate a single round of receptor-mediated entry of HCVpp into hepatoma cells, which can be quantified by reporter gene expression. These HCVpp have been employed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…However, mice sera can contain viral inhibitory components that can interfere with neutralization assays as reported for HIV-1 [ 46 ]. To test this, we first performed a small pilot HCV pseudoparticle (HCVpp) neutralization assay [ 64 ] using three serum samples from mice immunized with DREP-HCV/MVA-HCV, MVA-HCV/MVA-HCV and MVA-WT/MVA-WT [ 25 ]. We found that even a negative control serum (MVA-WT/MVA-WT) showed ~50% neutralizing activity at a 1/20 dilution, while the purified IgG samples did not ( Figure 8 B).…”
Section: Resultsmentioning
confidence: 99%
“…However, mice sera can contain viral inhibitory components that can interfere with neutralization assays as reported for HIV-1 [ 46 ]. To test this, we first performed a small pilot HCV pseudoparticle (HCVpp) neutralization assay [ 64 ] using three serum samples from mice immunized with DREP-HCV/MVA-HCV, MVA-HCV/MVA-HCV and MVA-WT/MVA-WT [ 25 ]. We found that even a negative control serum (MVA-WT/MVA-WT) showed ~50% neutralizing activity at a 1/20 dilution, while the purified IgG samples did not ( Figure 8 B).…”
Section: Resultsmentioning
confidence: 99%
“…HCVpp neutralization assays. Neutralization assays were performed as previously described (44). Huh7.5 cells were plated on wells of sterile 96-well plates (Corning) precoated with collagen solution (0.01%, MilliporeSigma) at a density of 1 × 10 4 cells/well.…”
Section: Discussionmentioning
confidence: 99%
“…This is problematic for vaccine screens and antibody-neutralizing breadth studies, as only strains that recover workable infectivity are included in such analyses and they may not necessarily be representative of the diversity circulating in the population. Moreover, some infectious strains give low yields, which fail to reach a signal-to-noise threshold sufficient for neutralization analysis, a signal at least tenfold above background is favoured but can be lowered to a minimum of 5 for clinical isolates [30,51]. Perhaps owing to its flexibility, several studies have demonstrated the HCVpp system is amenable to optimization.…”
Section: Discussionmentioning
confidence: 99%